Seagrass restoration in a high-energy environment in the Western Indian Ocean. (5th November 2022) - Wegoro, January; Pamba, Siajali; George, Rushingisha; Shaghude, Yohanna; Hollander, Johan; Lugendo, Blandina
Abstract: Although seagrass restorations have been conducted in many regions globally, restorations in high-energy wave environments are less explored. With accelerating losses of seagrass meadows globally, we also lose valuable ecosystem-based adaptations and ecosystem services, where the Western Indian Ocean is not an exception. The coast of Tanzania has only a few island shelters, creating an open exposed coast with a long wind fetch, generating strong wave exposure on the coastline. Still, seagrass meadows are present but have similar to global trends declined due to e.g. warmer ocean temperatures, coastal developments and destructive fishing methods. In view of the above challenges, there is a strong need for restoring seagrass meadows along the coast of Tanzania and the Western Indian Ocean (WIO) at large. However, restoration studies in the WIO are scarce and generally lacking in Tanzania. Studies elsewhere have shown that the success of a seagrass restoration varies significantly among trials and is to a large extent subject to the choice of a planting technique. Thus, in order to initiate the best practice for seagrass restoration in the Western Indian Ocean Region, for high-energy wave intertidal environments, we contrasted two restoration techniques, the plug and the sprig methods. We further explored different anchoring techniques and how various physical environmental factors influenced the growth and survival rates of seagrass shoots and rhizomes. We found that Syringodium isoetifolium transplants survived poorly in the sprig method (median = 0%), while the plug method demonstrated a much higher survival (median = 33.3%) for the 7 cm plug, and 66.7% for the 10 cm plug. The study also revealed a strong effect of water depth, where survival and growth parameters decreased with increased water depth. Finally, the study found a number of significant correlations, both positive and negative, between growth parameters and the measured environmental factors – and revealed that most of the measured environmental parameters were influenced by the local weather conditions and the monsoon seasonal cycling. The study illustrates that the restoration technique is strongly related to restoration success, providing clear guidance for future seagrass restorations in high-energy coasts in the Western Indian Ocean. Highlights: Survival rate of seagrass transplants was higher in the plug method than in the sprig method. Seagrass survival rate as well as shoot and rhizome growth rates were higher in 10 cm than in 7 cm plugs. Seagrass survival and growth rates were higher in the middle intertidal zone and decreased with increasing depth. Shoot and internode plastochrone intervals were higher in 10 cm than in 7 cm plugs, and increased with increasing depth. This is the first seagrass restoration study to be conducted in Tanzania.